ENABLING SUSTAINABLE PROCUREMENT OF BUILT ASSETS IN AFRICAN UNIVERSITIES: PERSPECTIVES OF FACILITIES’ DIRECTORS - Bankole AWUZIE; Fidelise EMUZE (Journal of Construction Project Management and Innovation)
The commitment of Higher Education Institutions (HEIs) to Sustainable Development (SD) seems to be yielding limited results. This is evident in the procurement and delivery of built assets within HEIs in Sub-Saharan Africa (SSA). This study reports on facilities directors’ perceptions of the challenges to sustainable procurement in HEIs within SSA. The identification of such challenges would contribute, significantly, to the extant discourse on how to stem the drift. A qualitative phenomenological research design is utilised. Forty-Three HEIs across two different countries in SSA- Nigeria and South Africa were selected based on purposive and convenience sampling. Facilities directors in these HEIs were interviewed through face-to-face and telephone interview sessions. Documents and webpages concerning the procurement of such buildings were also reviewed. Emergent data from these sources were thematically analysed. Findings indicate that Business As Usual (BAU) mode of procurement has remained the norm in most of the HEIs in spite of their professed commitment to SD. Challenges identified include: the seeming obsession of HEIs, acting as clients, with low front-end cost of project delivery; poor awareness of what SP entails; absence of skills required to champion the cause of SP within such HEIs, and non-specification of SD based requirements in the contracts documents. It is expected that this study would contribute to deepening existing knowledge concerning implementation of SD in HEIs in SSA.